2018
DOI: 10.18203/2320-6012.ijrms20180280
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of neoplastic lesions of female reproductive system-a two-year experience in Eastern Nepal

Abstract: Background: Neoplastic lesions of female reproductive system (FRS) consist majority of surgical cases. The aim of this study is to find out the frequency distribution of tumors occurring in FRS.Methods: This is a retrospective study carried out in Birat Medical College, situated in eastern Nepal. All formalin fixed surgical specimen of FRS from August 2015 to September 2017 were subjected for histopathology and examined under light microscopy. All neoplastic lesions were included, and non-neoplastic lesions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…Similar observations were also noted in the study by Khandekar S et al (6.28%) [15] while other studies by Gaikwad SL et al [12] , Singh M et al et al [16] and Paul SN et al [13] reported squamous cell carcinoma as 9.28%,7.04% and 7% respectively. In our study, the other histological variant of cervical carcinoma reported was a single case of small cell carcinoma in the age group of 41-50 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar observations were also noted in the study by Khandekar S et al (6.28%) [15] while other studies by Gaikwad SL et al [12] , Singh M et al et al [16] and Paul SN et al [13] reported squamous cell carcinoma as 9.28%,7.04% and 7% respectively. In our study, the other histological variant of cervical carcinoma reported was a single case of small cell carcinoma in the age group of 41-50 years.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Dhakal HP et al [17] also noted various other less common histological types of cervical carcinomas out of all the cervical cancers (1293 cases) in their study namely adenocarcinoma (3.8%), small cell carcinoma (0.3%), adenosquamous carcinoma (0.2%) and carcinosarcoma (0.2%) whereas in a study by Rahman MA et al [18] , cervical adenocarcinoma (1.08%) out of 62 cases of gynecological cancers, was also found other than squamous cell carcinoma. [12] Khandekar S [15] Singh M et al [16] Paul S N et al [13] Cervix (squamous cell carcinoma) 5.51% 9.28% 6.28% 7.04% 7% Endometrium (adenocarcinoma) 4.82% 2.14% 3.38% --Ovary (mucinous cystadenocarcinoma) 0.68% 0.71% 0.96% --…”
Section: Discussionmentioning
confidence: 99%